Ø£ØµÙˆÙ„ Ø§Ù„ØªÙØ³ÙŠØ± Ø¹Ù†Ø¯ Ø¹Ø¨Ø¯ Ø§Ù„Ù„Ù‡ Ø¨Ù† Ø¹Ù…Ø± Ø±Ø¶ÙŠ Ø§Ù„Ù„Ù‡ Ø¹Ù†Ù‡Ù…Ø§ ÙÙŠ ØªÙØ³ÙŠØ± Ø§Ù„Ù‚Ø±Ø¢Ù† - Nirwana AN, Andri (Jurnal Ilmiah Peuradeun, 2014)
Basically, ushulut tafsir is the science of Tafsir that describes the methods used by the ancient interpreter in the digging secrets contained in the Qur'an in order to know the laws of the Shari'ah, and bring benefit intended by Al-Qur 'an. In this case, the science of Tafsir is a collection of rules and foundations that help the interpreter to explore the secrets of the Qur'an according to the human ability to uncover the lessons, as well as the validity level, arguments from the Qur'an. In this case, the science of Ushul commentary explains the meaning of understanding, experiences and secrets of the Qur'an and determine methods to figure it out, and put the rules and principles that interpreter can execute these methods in his interpretation.